Compaction trends of permeability in artificial shales measured using pressure-oscillation technique - Beloborodov, R.; Pervukhina, M.; Lebedev, Maxim (2017)
Hydraulic permeability compaction trends in shales are poorly known due to shale diverse mineralogical composition and abundance of clay fraction. The conventional laboratory techniques for permeability measurements are time consuming and often inapplicable to tight rocks such as shales. We demonstrate feasibility and describe the methodology for laboratory acquisition of permeability compaction trends. For the first time, the pressure-oscillation technique is used during experimental mechanical compaction of artificial siltclay mixtures. We show that reliable permeability compaction trends may be acquired in a short time (two days per a sample). An exponential decay of permeability with the porosity decrease is observed on both compacted samples. Although the acquired permeabilities are in an agreement with porosity-permeability trends of natural shales, further compaction experiments with other clay minerals (e.g. smectite) will allow more accurate modelling of compaction trends of permeability in shales.